Estimation of Ziprasidone Hydrochloride Monohydrate in Bulk and Capsules by Reverse Phase HPLC - B. Sudha Rani; P. Venkata Reddy (E-Journal of Chemistry)
A reverse phase HPLC method is described for the determination of Ziprasidone HCl mono hydrate in bulk and pharmaceutical dosage forms. Chromatography was carried out on an ODS C18 column using a mixture of methanol and phosphate buffer (55:45v/v) as the mobile phase at a flow rate of 1mL/min. Detection was carried out at 314nm. The retension time of the drug was 4.522 min. The method produced linear responses in the concentration range of 0.5-30 μg /mL of Ziprasidone HCl mono hydrate.The method was found to be applicable for determination of the drug in capsules.